Climate Change and Globalization: Food Security in the Caribbean - Donna Miller (Caribbean Studies Students' Union, 2023)
Climate change and food security are among the world's biggest challenges. A growing population and climate change means that vulnerable regions such as the Caribbean, will continue to face unique strains. The effects of climate change are associated with poverty and a decrease in food security because of the decline in food production and access to a sufficient amount of nutritious food. Trade liberalization increases the number of challenges experienced by notably, the local Caribbean agricultural sector and has devastating effects on food security and rural livelihoods. Reductions in crop diversity and production mixed with low household incomes results in changed diets. These changes have increased the prevalence of non-communicable diseases (NCDs) such as diabetes and hypertension as well as obesity and other long-term health problems. Current and proposed strategies to aid with the challenges of climate change include further research on the creation of heat tolerant cattle breeds, technological developments, micro-insurance interventions, and the expansion of greenhouse farming. The traditional and acquired knowledge and skills of individuals in the agricultural sector is fundamental in creating strategies to adapt to the impacts of climate change and it is essential to ensure the strengthening of food security and food sovereignty. Financial resources in the Caribbean are inadequate and therefore, it is imperative that the Global North pay their dues in shouldering the responsibility of reducing the economic and environmental vulnerabilities in the Caribbean.